Proceedings of 18th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.1996.656849
|View full text |Cite
|
Sign up to set email alerts
|

Non-conscious and automatic acquisition of body and excreta weight together with ballistocardiogram in a lavatory

Abstract: For the purpose of health care monitoring during daily life, we attempted to devise a non-conscious monitoring system, set up in a lavatory, for the automatic acquisition of body weight, weight of urine and feces, together with ballistocardiogram as an index of cardiac function during relieving nature. The system consists of (i) a weight measuring platform(WMP) in which 4 load sensors were installed, and (ii) a data processing, displaying & storing(PDS) unit. The platform was placed on the floor adjacent to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The ballistocardiogram (BCG) signal has been measured using instrumented chairs [8]–[10], weighing scales [11]–[13], beds [14]–[16], and force plates [17], [18], all of which can potentially be integrated into patients’ homes. Additionally, researchers have demonstrated that the BCG signals contain clinically-relevant information regarding cardiac output (based on the rms power of the BCG [12]) and myocardial contractility (based on the R-J interval, the time delay between the electrocardiogram, ECG, R-wave and the BCG maximum peak, the J-wave [19], [20]).…”
Section: Introductionmentioning
confidence: 99%
“…The ballistocardiogram (BCG) signal has been measured using instrumented chairs [8]–[10], weighing scales [11]–[13], beds [14]–[16], and force plates [17], [18], all of which can potentially be integrated into patients’ homes. Additionally, researchers have demonstrated that the BCG signals contain clinically-relevant information regarding cardiac output (based on the rms power of the BCG [12]) and myocardial contractility (based on the R-J interval, the time delay between the electrocardiogram, ECG, R-wave and the BCG maximum peak, the J-wave [19], [20]).…”
Section: Introductionmentioning
confidence: 99%
“…A similar system appeared around 1996, also describing ECG and weight measurements utilizing a toilet seat [27]. The system was then extended to include ballistocardiogram measurements and introduced a patient identification by means of an RFID chip mounted in a pair of slippers [17].…”
Section: Establishing a Toilet For Measurementsmentioning
confidence: 99%
“…al. [5] proposed to attach balloon and reflective photoelectric sensor on toilet seat to obtain blood pressure as shown in figure 3. The proposed system obtains blood pressure without attaching anything on targeting person.…”
Section: Electrocardiogrammentioning
confidence: 99%
“…Networked ubiquitous sensors can keep eyes on one's biological signals unconsciously. Thus, foregoing researches have proposed and developed numerous unconstrained biological signal sensors, such as blood pressure meter on toilet seat [5], electrocardiograph on bed sheet [3], electrocardiography on wheel of a car [6]. Even some research mentioned possibilities of non-contact monitoring of activity of organs using ultra-wide-band (UWB) radar technique [2].…”
Section: Introductionmentioning
confidence: 99%